Improved Early Detection of Stroke By FAST Method in Kebraon Village Surabaya - Huda, Nuh; Delita, Selvi Karunia (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
Ignorance of the community about the signs and symptoms of stroke can cause delays of patients stroke be carried to the hospital. FAST (Face, Arm, Speech, Time) is an easy way to identify the symptoms of stroke, causing an increasing number of stroke cases in the community. The purpose of this research is identifying Effect of Health Education about FAST to Knowledge Early Detection of Stroke to The Cadres in Kebraon Village Surabaya.The MethodsThe Design of this research used Pre-experimental with One Group Pretest-Posttest Design approach. The Variable of independent is health education about FAST and the variable of dependent is knowledge early detection of stroke. The number population of health cadre in Kebraon Village is 164 people used Simple random sampling techniques as much as 116 respondents health cadres. The instrument used a questionnaire sheet. Data were analyzed with the Wilcoxon signed rank test.The results showed before being given health education about FAST, the knowledge of cadres majority is deficient. But after being given a health education about FAST, the knowledge of cadres majority is good. Wilcoxon signed rank test indicated the value of health education about FAST to knowledge early detection ofÂ stroke Ï = 0.000 â‰¤ Î± = 0.05. Conclusion The implication result of the this research showed an enhancement knowledge of early detection of stroke on cadres. Be expected enhancement knowledge to community about early detection of stroke with FAST.Keywords: FAST, Knowledge of Early Detection of Stroke, Cadres